Riehle, Alexander, ed. (2020). A Companion to Byzantine Epistolography. Leiden; Boston: Brill. XII + 531 pp. ISBN 978-90-04-41369-6 - Fonseca , Rui Carlos (CEM – Cultura, Espaço & Memória, 2023)
DOI: https://doi.org/10.21747/2182-1097/cem15r1